Health related quality of life and perception of deformity in patients with adolescent idiopathic scoliosis - (:unkn) unknown (IOS PRESS, 2017)
BACKGROUND: Quality of life and cosmethic appearance have gained importance as outcomes in AIS treatment. Improving aesthetic appearance and quality of life are defined as the primary aims of scoliosis treatment by health professionals. Studies that assess and compare the different treatment results in the field of quality of life and cosmethics are some what limited. OBJECTIVE: A cross-sectional study was designed to compare quality of life and deformity perception in patients with adolescent idiopathic scoliosis (AIS) received conservative (exercise or exercise +brace) or surgical treatment. METHODS: A total of 68 (58 females) patients aged 10-18 years with AIS received conservative (exercise or exercise+brace) or surgical treatment were invited to participate in the study. Quality of life (Scoliosis Research Society-23 (SRS-23)) and perception of deformity (Walter Reed Visual Assessment (WRVAS)) were assessed. RESULTS: Conservatively treated patients had significantly superior scores in function domain of SRS-23 than surgically treated patients (exercise/surgery, exercise+brace/surgery; p = 0.009, 0.004). Otherwise, surgically treated patients had significantly superior scores in self-image (p = 0.000, 0.000), and satisfaction with management (p = 0.001, 0.006) domains of SRS-23, and WRVAS (p = 0.000, 0.000) than conservative groups. CONCLUSION: In addition to radiographic assessments, quality of life, aesthetic perception, functionality, satisfaction with management, psycho-social status should carefully be taken into consideration by health professionals in the teratment of AIS.
Keywords: Adolescent idiopathic scoliosis; quality of life; perception; exercise; brace; surgery; BRACE; VALIDITY; QUESTIONNAIRE; RELIABILITY